An Assessment of Determinants and Consequences of Female Involvement in Crime in Nigeria in a Covidom - Inyang Martins Nyen; Umari Frances Ejue (Randwick International of Social Science Journal, 2022)
The wave of crimes involving the female gender globally and locally is unprecedented in recent times. This has left scholars to worry more about the sanctity of womanhood. The phenomenon poses a tough challenge to the moral rectitude of the family institution; this is against the backdrop of long-held notion that unarguably, the woman cross-culturally is the major custodian of the all-important society’s fibre. The objective of this study is to investigate the determinants and consequences of female involvement in crime and its impact on the wellbeing of society. The study was a survey, relying on secondary data. The study was anchored on General Strain theory of crime. Besides poverty, unemployment and feminist movement as causal determinants, it was also revealed that the phenomenon of female criminality has a huge dent on the moral fibre of society. Findings also show a causal relationship between family disintegration and female criminality. It was thus recommended that stakeholders and policy makers should find ways to strengthen the family institution thereby curbing criminality in the society.